2006
DOI: 10.1073/pnas.0605225103
|View full text |Cite
|
Sign up to set email alerts
|

Evolving resistance to obesity in an insect

Abstract: Failure to adapt to a changing nutritional environment comes at a cost, as evidenced by the modern human obesity crisis. Consumption of energy-rich diets can lead to obesity and is associated with deleterious consequences not only in humans but also in many other animals, including insects. The question thus arises whether animals restricted over multiple generations to high-energy diets can evolve mechanisms to limit the deposition of adverse levels of body fat. We show that Plutella xylostella caterpillars r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 45 publications
4
100
0
6
Order By: Relevance
“…The negative correlation between weight and larval survival reported above could be the mechanism of selection for lower weight on a laboratory diet. This observation is consistent with observed rapid adaptation to laboratory diets seen in other systems (Warbrick-Smith et al 2006). However, also note that the canonical lab strains (Oregon R and Canton S, Figures 1 and 2) tended to have relatively high weights and pupal survival and low triglyceride content, hemolymph sugar concentration, and larval survival, which cautions against the assumption that metabolic regulation in standard lab strains is fully representative of the normal range of physiologies found in nature.…”
Section: Sources Of Phenotypic Variationsupporting
confidence: 58%
“…The negative correlation between weight and larval survival reported above could be the mechanism of selection for lower weight on a laboratory diet. This observation is consistent with observed rapid adaptation to laboratory diets seen in other systems (Warbrick-Smith et al 2006). However, also note that the canonical lab strains (Oregon R and Canton S, Figures 1 and 2) tended to have relatively high weights and pupal survival and low triglyceride content, hemolymph sugar concentration, and larval survival, which cautions against the assumption that metabolic regulation in standard lab strains is fully representative of the normal range of physiologies found in nature.…”
Section: Sources Of Phenotypic Variationsupporting
confidence: 58%
“…One mechanism that may have allowed such change could be selection for different utilization efficiency of carbohydrates [16]. Flies maintained on the protein-enriched diet have experienced relatively low access to easy accessible energy sources (carbohydrates).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial selection experiments have also shown that the selection response is dependent on the nutritional environment, for instance in mice selected for larger body size [15]. Within insects, studies have used experimental evolution to study the impact of diet composition and it has been shown that rearing under alternative diet regimes for multiple generations results in genetically based changes in life-history traits [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…An example of how postingestive responses can change over generations in response to a shift in the nutritional environment comes from the work of Warbrick- Smith et al (2006), who reared multiple lines of the diamondback moth, Plutella xylostella, for eight generations either on a carbohydrate-rich or a protein-rich diet. The carbohydrate-rich diet comprised either chemically defined artificial food or a high-starch mutant of the plant Arabidopsis.…”
Section: Evolving Postingestive Responsesmentioning
confidence: 99%